LEGAL ANALYSIS OF MOTOR VEHICLE INSURANCE OWNERSHIP REVIEWED FROM KUH - Arman Syah Putra; Yelli Aswariningsih; Randy Napitupulu; Safrizal, Safrizal (Journal of Innovation Research and Knowledge, 2022)
The background of this research is how to analyze the ownership of auto insurance for motor vehicles in terms of various things. One of them is people and how the rights and responsibilities of motor vehicle insurance are. The method used in this research is to use the literature study method and the literature method by reading many journals and many articles containing laws relating to insurance and ownership of motorbikes and add to the repertoire of author knowledge. The problem raised in this study is how to find out the analysis of insurance ownership on motorized vehicles with the rights and obligations of the insurance holders so that they are in accordance with applicable law. The purpose of this study is how to know the rights and responsibilities of insurance holders, especially two-wheeled motorized vehicles.